1983
DOI: 10.1073/pnas.80.6.1721
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor (CRF)-like immunoreactivity in the vertebrate endocrine pancreas.

Abstract: The light microscopic immunocytochemical localization of corticotropin-releasing factor (CRF) is described in the endocrine pancreas of several species representing the major classes of vertebrates: fishes (channel catfish, Ictalurus punctatus), amphibians (African clawed toad, Xenopu8 laevis), reptiles (chameleon, Anolis carolinensis), birds (chicken, Gallus domesticus), and several mammals (rat, mouse, cat, rhesus monkey, and man). The CRF-containing cells are scattered over the entire islet tissue in primat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…Possible tissue sources for bombesin immunoreactivity in milk may be neural or extraneural tissue or both. For example, several known neuropeptides, thyrotropin-releasing hormone (56), somatostatin, corticotropin-releasing factor (57), and prolactin (58), are also found in the pancreas. Even GRP (59,60) and other bombesin-like peptides (60,61) are apparently associated with nerve tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Possible tissue sources for bombesin immunoreactivity in milk may be neural or extraneural tissue or both. For example, several known neuropeptides, thyrotropin-releasing hormone (56), somatostatin, corticotropin-releasing factor (57), and prolactin (58), are also found in the pancreas. Even GRP (59,60) and other bombesin-like peptides (60,61) are apparently associated with nerve tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, other lines of evidence suggest that CRF is expressed in organs outside the brain and might be released to act locally. CRF-IR was reported to be expressed in the digestive system (Petrusz et al, 1984;Suda et al, 1984;Wolter, 1984;Kawai et al, 1985;Kawahito et al, 1994), in endocrine organs (Petrusz et al, 1983;Suda et al, 1984), and by immune/inflammatory cells (Karalis et al, 1997).We found that CRF-IR neurons did not express IR for the CRF 1 receptor subtype, which is the functional receptor for CRF in the ENS (Liu et al, 2005). CRF 1 -IR was expressed in subgroups of neurons, which expressed chemical codes that were different from the codes for CRF-IR neurons.…”
mentioning
confidence: 99%
“…This strongly suggested an alternative, non-hypothalamic origin of irCRF-41 present in the systemic circulation. Multiple sources of peripheral irCRF-41 may be Postulated on the basis of immunohistochemical or content studies (18)(19)(20)(21)(22)(23)(24). Of particular interest were the adrenal glands, which contain and secrete CRF-like immunoreactivity (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, peripheral irCRF-41 appears to be derived from the placenta (18)(19)(20). The source of peripheral irCRF-41 in non-pregnant animals is unknown and it has been postulated that it may reflect, at least in part, hypothalamic irCRF-41 secretion (13,14,16,17); other sources include the gastrointestinal tract (21), the pancreas (22) and the adrenal gland (23,24). In the present study, the relationship between peripheral and hypophysial-portal plasma concentration profiles of irCRF-41 was evaluated by direct measurements in both circulatory compartments under a variety of experimental conditions.…”
mentioning
confidence: 99%